Zrównoważony rozwój ekonomiczny w rozwoju regionów - Passella, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Public R+D expenditures are one of the most effective ways to support the competetiveness and sustainable development. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 164-170